Magnetostratigraphy of eastern Iceland (Dataset) ... - N. D. Watkins; G. P. L. Walker (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Magnetostratigraphy of eastern Iceland ...